The peculiarities of modern pedagogical technologies development - Молчанова, Алевтина Олександрівна (Pedagogy of Higher and Secondary Education, 2015)
Molchanova A. O. The peculiarities of modern pedagogical technologies development. The main changes in education since the beginning of the 20th century that contributed to the introduction and development of pedagogical technologies are reviewed in the article. The characteristics of certain technologies are given. The main trends of using and improving pedagogical technologies in educational process are defined.